National Workshop on Anticipatory Action for Disaster Mitigation in Sri Lanka - Alahacoon, Niranga; Amarnath, Giriraj; Gnanatheepan, W. (International Water Management Institute, 2023)
The workshop addressed how Anticipatory Action (AA) strengthens the disaster preparedness in Sri Lanka's vulnerable community for flood and landslide disasters, especially during monsoon seasons. World Vision Lanka, with support from stakeholders like the Disaster Management Centre and the National Building Research Organization, is implementing an Anticipatory Action for Disaster Mitigation Project in Nuwara Eliya. Collaborating with the International Water Management Institute (IWMI), they pilot the approach in a drought-prone area, integrating it into the "AWARE" platform for enhanced coordination. The workshop aimed to share project findings discuss the way forward, and feature insights from key figures. The panel discussion delved into necessary governmental initiatives, early warning system enhancements, and the role of civil society in mitigating slow-onset disasters. The event concluded with plans for a national AA dialogue platform, working group establishment, inclusive implementation, and continuous sharing of project experiences. The proactive nature of Anticipatory Action and its potential to enhance disaster preparedness at the national level was emphasized.